MEASURING THE STUDENTS’ PERCEPTION OF SERVICE QUALITY - Kurniawan, Leonardi Lucky; ., N. Purnomolastu (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2012)
Like in many other countries, higher education institutions in Indonesia are facing intense competition as the higher education market becomes globalized and competitive pressure intensifies. It is essential that higher education institutions continually monitor the quality of their services and commit themselves to continuous quality improvements in order to respond to the needs of their stakeholders. Measuring service quality in higher education is thus essential In order to provide a comprehensive view of the quality of education, it is valuable to assess not only student perceptions of their educational outcomes but also their perceptions of the manner in which polytechnic education is provided.This study aims at measuring the students’ perception of the service quality of education in a department; identifying differences of the student perception on the service quality based on their academic profiles; identifying which service attributes are more influential in providing service in higher education; and offering recommendation to the management which area(s) still need(s) some improvement.Using the 5-scale questionnaires, the researchers collected the data for the study from graduates of the 5 departments- Accounting, Marketing Management, Secretary Foreign Business Language and Taxation. Pearson Chi-Square and Alpha Cronbach techniques were used to test the validity and reliability before analyzing the data from the questionnaire. Descriptive statistics was deployed to find out the mean value of each indicator. This was followed bv Dummy Regression analysis. JThe findings of the study suggest that faculty plays the most prominent indicator in reflecting the students perception of service quality of department.